2019
DOI: 10.1039/c9ob00596j
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative sulfonamidomethylation of imidazopyridines utilizing methanol as the main C1 source

Abstract: An efficient one pot, three component synthesis of C3 sulfonamidomethylated imidazopyridines has been disclosed utilizing methanol and DTBP as the major and minor methylene source, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…The rate of mycotoxin degradation was significantly lower in the methanol solution. It has been suggested that methanol is a free radical scavenger [ 94 ]; therefore, radicals generated by EB in methanol were scavenged by methanol molecules. It was concluded that solutions with radical scavenging ability need a higher EB dose.…”
Section: Electron Beam (Eb) Radiationmentioning
confidence: 99%
“…The rate of mycotoxin degradation was significantly lower in the methanol solution. It has been suggested that methanol is a free radical scavenger [ 94 ]; therefore, radicals generated by EB in methanol were scavenged by methanol molecules. It was concluded that solutions with radical scavenging ability need a higher EB dose.…”
Section: Electron Beam (Eb) Radiationmentioning
confidence: 99%
“…Off-white solid; 1.11 g, 70% yield; the eluent used was ethyl acetate/petroleum ether (55:45, v/v); mp = 180–182 °C (lit., 191–192 °C); 1 H NMR (400 MHz, CDCl 3 ): δ = 8.13 (d, J = 6.9 Hz, 1H), 7.82–7.79 (m, 2H), 7.70 (d, J = 9.1 Hz, 1H), 7.48–7.44 (m, 2H), 7.41–7. 37 (m, 1H), 7.31–7.24 (m, 3H), 6.87–6.83 (m, 2H), 6.78 (dd, J = 8.7, 1.2 Hz, 2H), 4.72 (s, 2H), 3.88 (br s, 1H); 13 C­{ 1 H} NMR (100 MHz, CDCl 3 ) δ = 147.6, 145.2, 144.7, 133.9, 129.4, 128.7, 128.3, 128.0, 124.9, 124.1, 118.4, 117.6, 116.4, 113.1, 112.5, 38.2; HRMS (ESI) calcd for C 20 H 18 N 3 + [M + H] + 300.1495, found 300.1498.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Recently, Ackermann and Wang groups independently developed C–H chalcogenation of indolines by copper and rhodium catalysis (Scheme b) . As a continuation of our interest in Cu-catalyzed reactions and novel methods for C–H functionalization, we herein report the first example of Cu-catalyzed regioselective C7 sulfonylation of indolines with readily available and environmentally benign arylsulfuryl chlorides via the directing group strategy.…”
Section: Introductionmentioning
confidence: 98%